MONITORING KELEMBABAN TANAH BERBASIS IOT MENGGUNAKAN ESP32 PADA KELOMPOK TANI SEKAR HANDAYANI KABUPATEN SORONG: ESP32-BASED IOT SOIL MOISTURE MONITORING SYSTEM FOR THE SEKAR HANDAYANI FARMER GROUP IN SORONG REGENCY - Haerunnisa; Indri Anugrah Ramadhani; Muhamad Ali Kasri (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
This study aims to design and implement an Internet of Things (IoT)-based soil moisture monitoring system using an ESP32 microcontroller in the Sekar Handayani Farmers Group in Sorong Regency. The main problem faced by farmers is the lack of accurate and regular soil moisture monitoring, which results in inaccurate watering and decreased crop productivity. The developed system utilizes a soil moisture sensor to measure soil moisture levels in real-time, then the data is processed by the ESP32 and sent via a Wi-Fi network to a cloud platform to be displayed on the monitoring dashboard. In addition, the system is equipped with a relay module and a water pump that allows the watering process to be carried out automatically based on soil conditions. The research method used is Research and Development (R&D), which includes the stages of needs analysis, system design, implementation, testing using the Blackbox Testing method, and system performance evaluation. The test results show that the system is able to read soil moisture conditions well, send data in real-time, and control the water pump automatically according to soil conditions (dry or wet). Based on the results of the user questionnaire using the Likert scale method, an average value of 88.7% was obtained, which is included in the very good category. Thus, this IoT-based soil moisture monitoring system using the ESP32 has proven effective in helping farmers monitor soil conditions, improving water efficiency, saving labor, and potentially improving the quality and productivity of agricultural produce.